The Candida auris Infection After the COVID‐19 Pandemic Seems to be an Urgent Public Health Emergency: A Call to Attention - Md. Ashrafur Rahman; Evangelos Victoros; Yeasna Shanjana; Marie Roke Thomas; Md. Rabiul Islam (Health Science Reports)
Abstract Background and Aims Inconsequential diseases can sometimes become extremely dangerous through mutation. Antifungal resistance has increased by 24%, and resistance only due to Candida auris (C. auris) species have increased by 60%. Here, we aimed to assess the knowledge of antifungal treatment and preventative measures to mitigate the consequences of infections caused by C. auris. Methods We performed a comprehensive literature search and gathered information for this review from publicly available published articles. We used C. auris, C. auris infection, mycoses, and antifungal resistance as search terms in Google Scholar, PubMed, and Scopus. We extracted the relevant information from the available article after careful evaluation. Results The genus C. auris was especially difficult to diagnose, as it was often mistaken for other types of yeast and led to incorrect treatment. The only effective method for diagnosing C. auris is through blood culture testing in laboratories and PCR tests. Because of its mutation, C. auris has grown increasingly resistant to all three classes of antifungals, with almost all strains resistant to fluconazole. These resistances were traced back to multiple‐point mutations in certain genes, such as ERG11 in the case of fluconazole and amphotericin B. In addition, C. auris is phylogenetically related to C. haemulonii, an emerging pathogen notably resistant to antifungals. So, it may be an evolutionary resistance that occurred earlier but has only begun to spread now. Echinoderm, a reliable treatment for C. auris infections showed ineffectively against FKS1 and ERG3 gene mutated Candida strains. Newly developed antifungal agents, like Ibrexafungerp, showed promising results against echinocandin‐resistant strains in clinical trials. Conclusion Without vaccines and effective treatment, its capacity to mutate and spread has detrimental effects on humans. Therefore, extensive research on drug development, quick, reliable diagnosis, and effective strategies for disease prevention and treatment are required to mitigate the health impact of C. auris.